Fast lithium-ionic conduction in a new complex hydride–sulphide crystalline phase. Issue 3 (6th November 2015) - Unemoto, Atsushi; Wu, Hui; Udovic, Terrence J.; Matsuo, Motoaki; Ikeshoji, Tamio; Orimo, Shin-ichi
Abstract : A new fast-lithium-ion-conducting crystalline phase formed from complex hydride and sulphide components was developed for all-solid-state batteries. Abstract : A new crystalline phase derived from a 90LiBH4 :10P2 S5 mixture displays high lithium-ionic conductivity of log( σ /S cm −1 ) = −3.0 at 300 K. It is stable up to 473 K and has both a wide potential window of 0–5 V and favorable mechanical properties for battery assembly. Its incorporation into a bulk-type all-solid-state TiS2 /InLi battery enabled repeated battery operation at 300 K.